Key concepts in theatre/drama education - Schonmann, Shifra; SpringerLink (Online service). (Rotterdam Boston SensePublishers, 2011)
Key Concepts in Theatre/Drama Education provides the first comprehensive survey of contemporary research trends in theatre/drama education.... Fifty seven entries, written by sixty scholars from across the world, aim to convey the zeitgeist of the field. The book's key innovation lies in its method of writing, through collaborative networking, an open peer-review process, and meaning-making involving all contributors.... The volume clearly shows that drama/theatre educators and researchers have created a language with its own grammar and lucid syntax. The concepts outlined convey the current knowledge of scholars, highlighting what they consider significant. Entries cover interdependent topics on teaching and learning, aesthetics and ethics, curricula and history, culture and community, various populations and their needs, theatre for young people, digital technology, narrative and pedagogy, research methods, Shakespeare and Brecht, other various modes of theatre and the education of theatre teachers.--From publisher descript
Electronic reproduction.
Keywords: Drama -- Study and teaching; Theater -- Study and teaching; Electronic books